Penerapan SIMKAPEL dalam Renewal Sertifikat Special Purpose Ship Safety (SPS) AWB. Rajawali Miracle oleh PT. Pelayaran Kencana Global Batam - Abdul Haris Damanik; Yursal Yursal; Netty Kesuma (Pusat Riset dan Inovasi Nasional, 2025)
Renewal of Special Purpose Ship Safety (SPS) certificates is a crucial process in maintaining the seaworthiness of Accomodation Working Barge (AWB) type ships, which function as residential residences for offshore workers. Certificates that have expired must be renewed through a renewal mechanism in accordance with shipping safety regulations. This study aims to examine the application of the Shipping and Maritime Information System (SIMKAPEL) in the process of renewing the SPS certificate of the AWB Rajawali Miracle ship by PT. The Batam Global Kencana Cruise is under the supervision of the Batam Special KSOP. SIMKAPEL as a digital platform from the Directorate General of Sea Transportation provides the convenience of certification services efficiently and transparently, allowing service users to access the status of the application at any time without having to be present directly at the office. The research method used is the field method (Field Research) through direct observation of the online submission process, physical examination of the ship, and issuance of certificates, as well as the library research method with literature studies from relevant sources. The results of the study show that SIMKAPEL is able to speed up the administrative process, improve data accuracy, and strengthen service transparency. These findings recommend the optimization of digital systems in ship certification services as a strategic step towards a modern and responsive transformation of maritime bureaucracy.